Penguatan Literasi Bahasa dan Digitalisasi untuk Pemberdayaan Masyarakat: Studi Implementasi Program Pengabdian Kepada Masyarakat di Desa Ujung Baji, Kabupaten Takalar - Nurasia Natsir; Muh. Fadli Faisal Rasyid; Muhammad Abbas; Khaeriyah Khaeriyah; Abdul Sahid (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2025)
In the digital 4.0 era, language literacy and digitalization are key elements in the process of community empowerment, especially in rural areas that still face the challenge of limited access to information and technology. This study aims to analyze the effectiveness of language literacy strengthening and digitalization programs in supporting community empowerment in Takalar Regency, with an integrative approach that considers local context and cultural wisdom. The method used is a qualitative approach through participatory action research, which allows for the active involvement of the community in the process of identifying problems and finding solutions. The community service activity (PKM) was held in Ujung Baji Village, Sanrobone District, Takalar Regency on July 10, 2025, involving 25 participants with diverse social and educational backgrounds. The literacy expert team from ADPERTISI plays a role in designing and implementing multilingual-based training programs and approaches that are sensitive to local culture. This program has succeeded in significantly increasing people's digital literacy, with 60% of participants able to utilize technology for MSME development and 40% of participants successfully accessing public services independently through digital platforms. The "Techno-Linguistic Integration" model applied has proven to be effective in overcoming language barriers in the digital technology adoption process. The integration of local languages with digital devices creates an inclusive and relevant learning environment for rural communities. The results show that a holistic and contextual approach to strengthening language literacy and digitalization can empower communities in a sustainable manner, strengthen local capacity, and encourage digital transformation at the grassroots level. These findings make an important contribution to the development of technology-based community empowerment strategies and local culture in the digital era.